Respostas

2014-03-18T21:37:51-03:00
c = 2,98 x 108 m/s                                            λ = 663 nm      →    6,63 x 10-7 m h = 6,63 x 10-34 J.s                                           hv₀= 0,369 eV    E = hv    →  E = h.()   →  E =   [6,63 x 10-34.()]    →    →  E = 2,98 x 10-19 J Convertendo J em eV, temos:                                                                                                                               E = 2,98 x 10-19 J   →   E = 1,86 eV     Tmáx =  hv - hv₀      Tmáx =  1,86  -  0,369 Tmáx = 1,491 eV